Molecular Detection of Bio Film Gene in Pseudomonas Aeruginosa Isolates from Tonsillitis - Enas Jalil Al-Mayali (Journal of Global Pharma Technology, 2018)
This study aimed to investigate Pseudomonas aeruginosa that cause surface and core tonsils from patients suffering from acute or chronic tonsillitis. A total of 130 samples represented by 100 sample from surface tonsillitis and 30 sample from core tonsillitis after tonsillectomy were referred to Al-sader medical city and Al-Hakim general hospital in Al-Najaf province (Ear, Nose and Throat unit), within period from September 2016 to February 2017.These patients ranged from 2-60 years .A (70) of them were males .A( 60 )were females.The result indicated , 25 from all surface tonsillitis were  pseudomonas aeruginosa ,but not present this bacteria in core tonsillitis .Genetic ,study some genes encoding to virulence factors and responsible for pathogenesis to Pseudomonas aeruginosa by using PCR and electrophoresis. The results indicated ,all P. aeruginosa isolate contain AlgD , RpoS gene that responsible for polysaccharide (alginate) and alpha factor in RNA polysaccharide and responsible for encoding many virulence factor respectively and present high percentage from PsIA ,PelA gene from P. aeruginosa isolate that encoding to biofilm formation .